Would placing pictorial health warnings on waterpipe devices reduce waterpipe tobacco smoking? A qualitative exploration of Egyptian waterpipe smokers’ and non-smokers’ responses - Mostafa, Aya (Tob Control, 2019)
BACKGROUND: Although Egypt places four generic pictorial health warnings (PHWs) on the front and back half of waterpipe tobacco packs (WTPs), waterpipe tobacco smoking (WTS) rates have continued to rise. It has been suggested that PHWs would be more salient if placed on the waterpipe device itself. This qualitative study explored how participants perceived the effects placing PHWs on waterpipe devices would have on warning salience and uptake or quitting of WTS. METHODS: We conducted 10 focus groups and 10 in-depth interviews with 90 adult waterpipe smokers and non-smokers, men and women, who lived in rural, semi-urban and urban regions of Egypt. We presented participants with four novel PHWs of different sizes positioned randomly at four locations on a waterpipe device (the glass body, metal holder, mouthpiece or hose), one at a time. At each session, participants viewed a PHW on all four locations. Novel warnings were shown on plain labels with a dark uniform background and featured pictures, text and the quitline number. Transcripts were analysed using thematic analysis. RESULTS: Participants thought placing PHWs on waterpipe devices might increase salience, prevent WTS initiation or trigger quit attempts; they favoured placing PHWs on the glass body, mouthpiece or waterpipe hose. Both waterpipe smoker and non-smoker participants thought these potential effects would affect non-smokers or non-established smokers more than established waterpipe users. CONCLUSIONS: Our exploratory study suggests that PHWs featured prominently on waterpipe devices could potentially deter experimentation with waterpipe tobacco products and promote cessation, especially among non-established users.